Bangladesh: Income Inequality and Globalization - Uddin, Md. Nezum (Asian Business Review, 2020)
Global anxiety about the effect of globalization is increasing. Throughout recent years the influence of globalization on income allocation has been fiercely discussed. This research carries out a time series review to examine the effect of globalization on income inequality in Bangladesh between 1975 and 2018. Study results indicate that globalization variables – exports, imports, foreign aid, foreign direct investment (FDI), and remittance inflows – have a significant long-term impact on income inequality in Bangladesh. Long-term foreign aid and imports are improving, while exports, FDI, and remittance inflows are deteriorating income distribution in Bangladesh during the study period. Nevertheless, in the short term, exports, imports, FDI have little to no impact in the model and a change in foreign aid and remittances will have a significant conservative force attempting to resolve the system.